Viability and Sustainability Assessment of the Mangrove Ecosystem: A Case Study of Sausu Tambu, Indonesia - Achmad Rizal; Muh. Saleh Nurdin; Sri Ningsih Mallombasang (Journal of Multidisciplinary Applied Natural Science, 2026)
The management of mangrove areas is often hindered by the lack of integrated information regarding the ecological conditions and the social aspects of the surrounding communities, as previous studies tend to evaluate both aspects separately. Viability assessment addresses ecological conditions and sources of threats, while sustainability emphasizes multidimensional management strategies. The integration of both is important to bridge ecological diagnosis with long-term management. The research was conducted on the Sausu Tambu mangrove ecosystem by integrating Conservation Action Planning (CAP) and Rapid Appraisal for Fisheries Sustainability (Rapfish). The methodological novelty lies in the two-step matrix that sequentially crosses the viability and threat scores of CAP with the sustainability index of Rapfish, resulting in a final status that reflects the ecological condition and institutional social capacity in an integrated manner. The findings show that this area has nine types of mangroves. The viability is rated as fair, and the threats are rated as medium, which assigns it a vulnerable CAP status. The ecological and social domains of Rapfish are at a moderate level (57.85% and 53.90%), while the institutional domain is slightly lower (49.64%). The intersection of the CAP status with the Rapfish index still results in a final vulnerable status. Actionable conservation strategies include the establishment of management bodies for village mangroves, formulation of village regulations, periodic planting and monitoring, environmental awareness and pride campaigns, inter-party cooperation, and community economic empowerment. These results have consequences for long-term coastal governance and support the Sustainable Development Goals, especially for ocean ecosystems through the protection of coastal habitats and for land ecosystems through the management of mangrove vegetation and biodiversity. The findings can also be used as a model for evaluating other small mangrove areas in Indonesia and tropical coastlines.